Activation of M1 Macrophages in Response to Recombinant TB Vaccines With Enhanced Antimycobacterial Activity - Yang, Shiu-Ju; Chen, Yih-Yuan; Hsu, Chih-Hao; Hsu, Chia-Wei; Chang, Chun-Yu; Chang, Jia-Ru; Dou, Horng-Yunn (Frontiers in Immunology, 2020)
Pulmonary tuberculosis (TB) is a difficult-to-eliminate disease. Although the Bacille Calmette–Guérin (BCG) vaccine against Mycobacterium tuberculosis (MTB) has been available for decades, its efficacy is variable and has lessened over time. Furthermore, the BCG vaccine no longer protects against newly emerged Beijing strains which are responsible for many current infections in adults. Development of a novel vaccine is urgently needed. In this study, we first tested the efficacy of our recombinant BCG vaccines rBCG1 and rBCG2, compared to parental BCG, against MTB strain H37Ra in mice. Both the bacterial load and the level of lymphocyte infiltration decreased dramatically in the three groups treated with vaccine, especially rBCG1 and rBCG2. Furthermore, the Th1 and Th17 responses increased and macrophage numbers rose in the vaccination groups. Th1-mediated production of cytokines TNF-α, IFN-γ and MCP-1 as well as M1-polarized cells all increased in lung tissue of the rBCG1 and rBCG2 groups. Clodronate-induced depletion of macrophages reduced the level of protection. Based on these results, we conclude that rBCG vaccines induce a significant increase in the number of M1 macrophages, which augments their potential as TB vaccine candidates.